2021
DOI: 10.1021/acs.inorgchem.1c00094
|View full text |Cite
|
Sign up to set email alerts
|

[(η6-p-Cymene)[3-(pyrid-2-yl)-1,2,4,5-tetrazine]chlororuthenium(II)]+, Redox Noninnocence and Dienophile Addition to Coordinated Tetrazine

Abstract: The bidentate ligand 3-(pyrid-2-yl)-1,2,4,5-tetrazine (TzPy) coordinated in the complex [CyRuCl­(TzPy)]­PF6 ([1]+; Cy = η6-p-cymene) shows noninnocent behavior and can be modified through the addition of dienophiles, vinylferrocene (ViFc) or ethynylferrocene (EthFc). The kinetics and transition-state thermodynamic analysis of the reaction of [1]+ + ViFc found ΔG ⧧(298 K) = 67 kJ mol–1, while that of [1]+ + EthFc was ΔG ⧧(298 K) = 83 kJ mol–1. The room temperature second-order rate of [1]+ + EthFc, k 2 = 1.51(4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…This reaction allows for efficient labeling with the metal complex, opening possible applications in the fields of chemical biology and medicine. Interestingly, Ringenberg et al describe an increase in rate constants of 2 orders of magnitude compared to the reaction of tetrazine itself. The same behavior was observed by the same group for a ruthenium complex . This acceleration makes these systems particularly interesting as it would allow for labeling at ultralow concentrations.…”
supporting
confidence: 77%
“…This reaction allows for efficient labeling with the metal complex, opening possible applications in the fields of chemical biology and medicine. Interestingly, Ringenberg et al describe an increase in rate constants of 2 orders of magnitude compared to the reaction of tetrazine itself. The same behavior was observed by the same group for a ruthenium complex . This acceleration makes these systems particularly interesting as it would allow for labeling at ultralow concentrations.…”
supporting
confidence: 77%
“…Rhenium tricarbonyldiimine complexes are an attractive class of electrocatalysts for probing the mechanistic pathways of reductive CO 2 activation owing to the wealth of literature precedent and their facile syntheses. The canonical [Re­(bpy)­(CO) 3 Br] ( 0 , where bpy = 2, 2′-bipyridine; Scheme ), for instance, has been shown to reduce CO 2 to carbon monoxide (CO) with 100% selectivity over proton reduction. ,, A two-electron reduction of the rhenium­(I) precursor yields a catalytically active anionic species that possesses a delocalized electron cloud and available π interactions from the equatorial carbonyl ligands, inducing the preferred formation of Re-CO 2 adducts over Re–H intermediates. , There is also a rich body of literature describing the in situ modification of redox-active unsaturated nitrogen-donor ligands under reducing or thermal conditions. , …”
Section: Introductionmentioning
confidence: 99%
“…The bulky ferrocenyl moiety was at the 5-position due to trapping of the kinetic product. [28] In a similar report on the addition of ViFc to [CyRuCl(TzPy)] + , Cy = η 6 -cymene, we found that dihydropyridazine could be oxidized to the pyridazine state of the ligand, [29] where [1H 2 Fc] did not show this apparent reactivity but did appear to slowly oxidize over the course of several weeks to [1Fc]. The pyridazine could, however, be generated by adding ethynylferrocene (EthFc) to [1] to give [1Fc] (Scheme 1).…”
Section: Introductionmentioning
confidence: 56%